Analisis Kerjasama Pemanfaatan Aset Daerah - Agung Prasetya; Siti Musyarofah; Bambang Haryadi (Universitas Trunojoyo Madura, 2020)
The purpose of this study is to understand and analyze the cooperation in the use of building assets in the XYZ Regency Government. This research uses descriptive qualitative method, the researcher tries to analyze the object of research in accordance with the facts in the field, process the data obtained from the informants and conduct observations and interviews and literature study. The results of this study indicate that cooperation in the use of these assets in terms of PAD is very small compared to the investment issued, and also found a lot of cheating in the management of this cooperation so that there is a strategy that must be done by the Government to optimize PAD by increasing the quality of human resources, and making improvements from themselves. and improvement of standard operating procedures (SOP).